INFORMATION RECYCLING MATHEMATICAL METHODS FOR PROTEAN SYSTEMS: A PATH-WAY APPROACH - Kumar, S. (The South African Journal of Industrial Engineering, 2011)
ENGLISH ABSTRACT: In this paper, a concept of information recycling mathematical methods has been introduced for mathematical modelling and analysis of problems arising in real life systems. Based on the proposed concept, an algorithm for solving a linear programming model arising in a protean environment has been discussed. This concept has been extended to consider the case of a quadratic programming model and a differential equation of the second order. It has been pointed out that the proposed concept is a challenge to reconsider other mathematical modelling and solution procedures in a protean environment. AFRIKAANSE OPSOMMING: Die beginsel van sikliese behandeling van inligting met behulp van wiskundige metodes en modelle word voorgehou vir die ontleding van praktykprobleme. Gebaseer op hierdie gedagte word ’n algoritme bespreek vir die oplossing van